Avaliação fisiológica da produção de soja Roundup Ready com aplicação do herbicida Glyphosate em campo - Antunes Junior, Mario Zortéa (2014)
Currently, the glyphosate resistant soybean (GRS) area reaches 85% of soybeans produced in Brazil. However, little is known about the physiological performance of GRS under field conditions, liable to water stress caused by dry conditions, which is quite common during the crop cycle. Thus, to knowledge the relationship between water stress and the effect of glyphosate on plant physiology of GRS is very important. Therefore, this study aimed to investigate the physiology of the GRS production under water stress in field conditions. For this, the TMG 115 RR soybean cultivar was planted in the experimental field of the UNIVAG – Centro Universitário de Vázea Grande, in Várzea Grande-MT, in a randomized blocks with three replications and factorial design (2x2), and the method of weed control (C) was made with glyphosate application or manual capping, and the hydrological regime (W), with or without interruption of irrigation, totaling four treatments. We evaluated the total dry matter, leaf area index, grain yield, leaf water potential, gas exchange, number and weight of nodules, specific leaf area, photosynthetic pigments content, leaf concentration of macro and micronutrients and photosynthetic capacity by A/Cc and A/PPFD curves. Increases were observed in the variables of gas exchange and photosynthetic parameters of A/Cc and A/PPFD curves under no restriction on soil water availability and glyphosate application, without, changing the leaf area index and specific leaf area. However, they were not sufficient to produce an increase in the grains yield and significant changes in leaf water potential. There was stomatal effects caused by glyphosate, observed by an increase in stomatal conductance, relationship between internal concentration and environment CO2, in the photosynthetic parameters of A/Cc and A/PPFD curves and reduction in the water use instatenous efficiency, that caused an increased in the water consumption by the culture. There was also a significant reduction in the number of nodules for treatments with glyphosate application as well as a trend towards the reduction in dry matter of nodules. Both water restriction as glyphosate application were not sufficient to alter the photosynthetic pigments concentration in the TMG 115 RR soybean leaf, although decreases in carotenoid pigment content in water stress conditions and glyphosate application were observed. Likewise, there were no significant reductions in foliar concentrations of macro and micronutrients studied in this work, although some elements, such as N, Ca, Fe and Mn exhibited a willingness to lower concentrations in the leaf tissue especially when under the influence of herbicide and in the absence of irrigation. Under water stress conditions and glyphosate application, decreases in photosynthetic capacity of the plant were observed, making the photosynthetic apparatus of GRS more sensitive to dehydration process.